The depressor mandibulae muscle in Anura - Manzano, Adriana Silvina (2002)
It is well known that the diversity in anuran cranial structure is large, observed in the variation of the bone structure and associated muscles. The depressor mandibulae is the jaw muscle that opens the mouth and was considered by many authors useful in delimiting anuran groups. However, there is still much controversy on the value of the m. depressor mandibulae as a relationship-indicating character. The goal of this project is to explore the morphological diversity of the depressor mandibulae muscle among different families of anurans. Specimens including 60 genera of 17 families of Anura were dissected, using traditional techniques of macroanatomy. Fifteen morphological groups can be distinguished within the anuran species analysed. The insertion point demonstrates little variation. The overall pattern of the origin is also quite stable, except for Hemisus g. guineensis, Arthroleptis and Breviceps poweri, which have an unusual anterior branch of m. depressor mandibulae coming from the maxilla. The great diversity in shape of the m. depressor mandibulae correlates with the plethora of patterns already mentioned for cranial morphology in Anura. However, it is difficult to assign a specific morphology to a given higher taxon. We also found no evidence that variations in the m. depressor mandibulae are associated with particular habits.